Translating the promise of 5HT4 receptor agonists for the treatment of depression - Murphy, SE; de Cates, AN; Gillespie, AL; Godlewska, BR; Scaife, JC; Wright, LC; Cowen, PJ; Harmer, CJ (Cambridge University Press, 2020)
Animal experimental studies suggest that 5-HT4 receptor activation holds promise as a novel target for the treatment of depression and cognitive impairment. 5-HT4 receptors are post-synaptic receptors that are located in striatal and limbic areas known to be involved in cognition and mood. Consistent with this, 5-HT4 receptor agonists produce rapid antidepressant effects in a number of animal models of depression, and pro-cognitive effects in tasks of learning and memory. These effects are accompanied by molecular changes, such as the increased expression of neuroplasticity-related proteins that are typical of clinically useful antidepressant drugs. Intriguingly, these antidepressant-like effects have a fast onset of their action, raising the possibility that 5-HT4 receptor agonists may be a particularly useful augmentation strategy in the early stages of SSRI treatment. Until recently, the translation of these effects to humans has been challenging. Here, we review the evidence from animal studies that the 5-HT4 receptor is a promising target for the treatment of depression and cognitive disorders, and outline a potential pathway for the efficient and cost-effective translation of these effects into humans and, ultimately, to the clinic.